The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/23259671211002280
|View full text |Cite
|
Sign up to set email alerts
|

Failure Rate After Superior Capsular Reconstruction With Achilles Tendon–Bone Allograft for Irreparable Rotator Cuff Tears

Abstract: Background: Superior capsular reconstruction (SCR) is an alternative to reverse shoulder arthroplasty for irreparable rotator cuff tears (IRCTs). The reconstructed capsule acts as a static restraint to prevent superior migration of the humeral head. Traditional SCR uses a fascia lata autograft, which has shown failure at the greater tuberosity. An Achilles tendon–bone allograft has been proposed to improve the failure rate. Purpose: To evaluate the surgical outcomes of SCR using an Achilles tendon–bone allogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, these satisfactory results run against the findings by Kholinne et al. 24 In a case series of 6 patients, the authors studied the validity of CalATA for superior capsular reconstruction in the management of irreparable massive cuff injuries. The rationale behind the study is based on animal studies 26 , 27 that showed that the healing process at the bone-to-bone interface is more favorable than at the tendon-to-bone interface.…”
Section: Discussionmentioning
confidence: 87%
“…However, these satisfactory results run against the findings by Kholinne et al. 24 In a case series of 6 patients, the authors studied the validity of CalATA for superior capsular reconstruction in the management of irreparable massive cuff injuries. The rationale behind the study is based on animal studies 26 , 27 that showed that the healing process at the bone-to-bone interface is more favorable than at the tendon-to-bone interface.…”
Section: Discussionmentioning
confidence: 87%
“…Graft integrity has been shown to be an important independent factor to improve postoperative outcomes after SCR, 22 and graft healing has been proposed to be critical in improving patient outcomes. 39 Ciampi et al 8 demonstrated that mesh augmentation of rotator cuff repair significantly improved the clinical outcomes and reduced the retear rate.…”
Section: Discussionmentioning
confidence: 99%
“…As such, we were able to employ our technique, in which we utilized the graft as an augmentation to a rotator cuff repair, with a large surface of contact between the native tendon and the allograft. This technique differs substantially from those of Kholinne et al, 15 who utilized the allograft tendon as an SCR, and Moore et al, 28 who sewed the allograft to the ends of the native rotator cuff tissue. The rotator cuff repair may explain the improved clinical outcomes, as well as the graft integration noted on histology.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies that have utilized an ATBA for SCR in irreparable rotator cuff tears. 15,16,24 Kholinne et al 15 published a case series of 6 patients with massive irreparable rotator cuff tears in which an ATBA was used for SCR. There was a high graft failure rate at 1 year (83%), and only 50% of the patients had improvements in the ASES scores that met the minimal clinically important difference of 21.0 points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation